A new species of Andinia (Pleurothallidinae, Orchidaceae) with unusual bearded flowers from Ecuador - Ponert, Jan; Andrade, Mario Portilla; Chumová, Zuzana; Trávníček, Pavel (Phytotaxa, 2020)
Andinia barbata is newly described based on cultivated material originally collected near Shaglli in Ecuador. It belongs to subgenus Aenigma and differs from all others in this group by the lanceolate lip, 2.5 times longer than wide, and unusually long and thick projections from the synsepal which gives a bearded appearance to the flowers. Phylogenetic placement under the genus is supported with reconstruction of a molecular phylogeny using nuclear ribosomal ITS and plastid matK regions and the genome size estimation (1C-value = 1.38 pg) is provided.